ANALISIS SEMIOTIKA TERHADAP PENGGUNAAN MEME TIKUS BERKEPALA PUAN MAHARANI - Aripai, Reski; Hayat, Nahrul (CORE: Journal of Communication Research, 2024)
Memes have become an inevitable digital cultural phenomenon on social media, serving not only as a source of entertainment but also as powerful communication tools. In the context of news, the use of memes provides not just additional visual elements but also the potential to influence public perception of the issues presented. This article proposes a semiotic analysis approach to understand how memes are utilized in news contexts. By considering the visual structure, iconography, and symbolism embedded within memes, semiotic analysis enables the uncovering of hidden meanings that reflect the social, political, and cultural contexts at the time of their creation. Through this study, the article aims to illustrate how memes can play a role in shaping public narratives and reflecting power dynamics and ideological conflicts within the realm of digital news.